Parkinson's Disease Database in the Middle East, North Africa, and South Asia Countries - Khalil, Hanan; Shraim, Mujahed; Jaradat, Bayan; Ibrahim, Riham Hussein; Kamel, Walaa A.; Khan, Shazma; Aldughmi, Mayis; Amer, Hanan; Al-Qassabi, Ahmed; Al-Sharman, Alham; Habib, Ahsan; Alakkas, Aljoharah; et al. (International Journal of Public Health, 2025)
Introduction: The prevalence of Parkinson's disease (PD) has seen a substantial rise throughout the Middle East, North Africa, and South Asia (MENASA) area, mostly due to shifts in population demographics and environmental influences. For this reason, the Consortium for Global Diversity in Parkinson’s Disease (CDG-PD) was established in 2020. CDG-PD comprises a network of Parkinson’s experts. The mission of the CDG-PDis “to improve the quality of care for people with Parkinson’s disease (PD).” Objectives: This study aims to establish a multicenter database to evaluate Parkinson's disease in the MENASA region in the context of expert care Methods: The CGD-PD consortium includes 20 institutes from 9 MENASA countries. The database collectscomprehensive data from PD patients. Discussion: Developing this database is a vitalfirst step toward PD treatment in the MENASA area. Information on the epidemiology, clinical traits, and treatment practices particular to this area will be made available bythe data. Conclusion: The CGD-PD database will be instrumental in addressing the gap in PD research in the MENASA region, ultimately improving the quality of life for PD patients